(untitled) (Zaporizhzhia Historical Review, 2021)
The article is about the social-economic state of scientists of Kiev, Kharkov and Novorossiysk universities in the second part of the 19th – beginning of the 20th century. The reasons influenced the economic condition of the academic staff, non-teaching support staff, professors’ grant-aided students, and not-staff lecturers have also been considered.